Characterizations of Size-segregated Ultrafine Particles in Diesel Exhaust - Jaehyun Lim; Cheolsoo Lim; Sungwoon Jung (Aerosol and Air Quality Research)
Abstract Size-segregated ultrafine particles (UFPs) in diesel exhaust were investigated to characterize carbonaceous substances, metals, and organic compounds originating from a medium-duty diesel engine dynamometer using the 13 driving mode. Organic carbon (OC) and elemental carbon (EC) peaked at 330–550 nm, but the OC/EC ratio showed two peaks in the ultrafine and accumulation modes. The distribution trend of metal elements was opposite to that of the size-segregated OC/EC ratio. The amounts of toxic Pb, As, and Cd were less than 0.03–2.5% in diesel exhaust particles (DEPs), but their cumulative fractions in the ultrafine mode exceeded 50%. Most organic compounds (76.6%) and alkanes (67.0%) were emitted in the accumulation mode (170–1000 nm). More than 70% of the identified polycyclic aromatic hydrocarbons (PAHs) were emitted in the accumulation mode (94–1000 nm), with phenanthrene being the most abundant. Two significant size ranges of toxicity equivalent quantity peaks in the ultrafine (34–66 nm) and accumulation (170–330 nm) modes were observed for the size-segregated DEPs. Contrary to the trends for PAHs and organic compounds, the identifiable nitrogen-containing polycyclic aromatic compounds were more abundant in the ultrafine mode. Overall toxicity was high as UFPs can be deposited with high efficiency throughout the human respiratory tract.